Adaptability of Wheat in Malaysia - Faruq, Golam (1999)
Wheat is a cool season crop, but its flourishes in many different agro-climatic zones and have the broadest adaptability compare to all other crops in the world. Recent advances in technologies for wheat production in humid tropical environments have promoted Malaysia to initiate research to develop technologies for domestic wheat production. This program places special emphasis on the identification of superior germplasm for further research in tropical Malaysia. A discoursing situation was observed during the 1st experiment (Benchmark study). Two hundred eighty eight germplasm accessions were used in this study and the results revealed that all germplasm accessions were affected with seedling blight, severe Helminthosporium leaf blotch and partially Fusarium head scab. All germplasms germinate well, but gradually more than 50% died within six weeks. Less tiller, short spike length, shriveled grain and high sterility were common constraints for good yield. A total of 288 germplasms were evaluated in first experiment and based on different characters 175 germplasms were selected and 34 of them produced grain. The scene was dramatically changed in the second experiment (2A), where 175 germplasm accessions were grown in 30 cm x 30 cm size polybag with four replications and a prescribed soil mixture of top soil. sand and peat soil with a ratio of 3:2:1 was used. Vegetative growth of all genotypes was normal with optimum number of tillers up to 11 and spike length up to 9 cm. A total of 40 genotypes produced grain in this study. Visual grain quality also improved compared with benchmark study. In the subsequent 3rd experiment (2B), again 175 germplasm accessions were used with same management practices to study further development of genotypes in different growing season time and comparison with the previous growing seasons. The same 40 genotypes only produced grain but the sterility level had changed in some genotypes. Results from 1st and 2nd growing seasons revealed that the agronomic characters were significantly influenced by different genotypes and a positive correlation confirmed that some quantitative characters like fertile tillers, grain per spike and 1000 grain weight are important characters having direct bearing on influencing plant yield. Forty germplasms which produced grain were selected and used in the final experiment. Helmmthosponum leaf blotch infestation was observed with a Disease index (01) range of I - 9. Seven genotypes were found with minimum infestation (01 -I). Six genotypes produced almost normal shiny grain but lower 1000 grain weight compared with original grain. However, based on yield contributing characters and grain quality, entries 13, 28, 31, 45, 58, 72, and 73 were identified as outstanding among the 175 genotypes. These lines seems to be more potential for further research in Malaysia and by introducing wheat as a new crop in Malaysia, it may eliminate an important part of the foreign exchange drain.